Oenothein B ameliorates hepatic injury in alcoholic liver disease mice by improving oxidative stress and inflammation and modulating the gut microbiota - Xu, Lu; Li, Wei; Chen, Shu-yi; Deng, Xi-wen; Deng, Wei-feng; Liu, Guo; Chen, Yun-jiao; Cao, Yong (Frontiers in Nutrition, 2022)
Introduction Alcoholic liver disease (ALD) is a global health problem for which there is no current food and drug administration (FDA)-approved therapy. Oenothein B (OEB) is a macrocyclic dimer ellagic tannin that possesses abundant biological activities including antioxidant, anti-inflammation, antitumor, immunomodulatory, and antimicrobial properties. Materials and methods In this study, the hepatoprotective effect of OEB against ALD was investigated in vivo and in vitro. Results We found that OEB treatment dramatically reduced alcohol-induced hepatic injury, as evidenced by decreased levels of aminotransferases and inflammatory biomarkers and increased antioxidant capacity in OEB-treated groups. Discussion OEB treatment alleviated oxidative stress by upregulating the Keap1/Nrf2 signaling pathway and inhibited inflammation by downregulating the TLR4/NF-κB signaling pathway. Additionally, OEB treatment positively improved alcohol-induced intestinal microbial dysbiosis by modulating the structure and composition of gut microbiota. Interestingly, we observed the increasement of short-chain fatty acid (SCFA) producers (Muribaculaceae) and the decreasement of Gram-negative bacteria (Akkermansia) in the OEB treatment groups, which may contribute to the inhibition of hepatic oxidative stress and inflammation via the gut-liver axis. In summary, our findings indicate that OEB is a promising therapeutic strategy for preventing and treating ALD.